Penerapan Metode Otak Kanan Menggunakan Buku Itmamul qiro’ah Mata Pelajaran Tahsin Al-Qur’an Kelas 2B SDIT Rasyid Sedayu - Yamin, Sabanul (STIT Darul Fattah Bandar Lampung, 2024)
ABSTRACT The application of this method is based on teachers who have never applied the right brain method in learning tahsin Al-Qur'an. This method is to help students learn to read the Qur'an through learning tahsin Al-Qur'an. The right brain method is an innovative approach to learning the Qur'an that optimizes the use of the right brain in a comprehensive, easy, and enjoyable way. The learning process uses the 5P method (Opening, Experience, Teaching, Assessment, and Closing) and the strains of the jiharkah tune. The results of the study indicate that the application of the right brain method using the Itmamul Qiro'ah Book for class 2B SDIT Rasyid Sedayu has gone well according to procedures, including planning, implementation, and evaluation. The enthusiasm of students in learning tahsin Al-Qur'an is also very high, as evidenced by the realization of learning manners such as listening manners when the speaker delivers the material, the activeness of students when answering questions, and most importantly, students can be orderly when the application of this method takes place. This achievement is certainly inseparable from the main supporting factors, which include: certified right-brain method speakers and the compilers of the Itmamul qiro’ah book itself, implementing a structured learning system, high student learning motivation, and adequate learning facilities. The inhibiting factor is that two students are difficult to condition and this is a challenge for the speakers to apply the right-brain method using the Itmamul qiro’ah book and maintain the learning motivation of other students